The (Un)real Existence of ADHD—Criteria, Functions, and Forms of the Diagnostic Entity - Honkasilta, Juho; Koutsoklenis, Athanasios (Frontiers in Sociology, 2022)
The contemporary conceptualization of Attention Deficit Hyperactivity Disorder (ADHD) as a complex, multifactorial neurodevelopmental disorder cannot be understood as such without a complex assemblage of political, economic, and cultural processes that deem the conceptualization to be valuable and useful. In this article we use the notion of psychiatrization as a lens through which to see parts of these processes that make up ADHD what it is. In the first part of the article, we critically assess the scientific basis of the ADHD diagnosis via examining its diagnostic criteria as presented in the current fifth edition of Diagnostic and Statistical Manual of Mental Disorders (DSM), the so called “Bible” of modern psychiatry. The second part of the article asks what is done with the ADHD diagnostic entity and with the idea that it represents a natural neurodevelopmental state within an individual—something an individual has—as represented in the DSM-5. Drawn from our previous research, we analyze how ADHD becomes real in discourse practice as a powerful semiotic mediator through analysis of the various functions and forms in which it takes shape in institutional, social, and individual levels. We conclude that the frequent changes in the diagnostic criteria of ADHD do not reflect any real scientific progress. Among other reasons, they change to match better the maneuvers of individuals when navigating an increasingly psychiatrized society in the search for recognition, support, category membership, immunity, sympathy, and sense of belonging.